Environmental Collaboration under Various Contracts in the O2O Closed-Loop Supply Chain - Yang Bai; Xueying Meng (Discrete Dynamics in Nature and Society)
This study considers the dynamic pricing and green advertising incentive decisions in the O2O closed-loop supply chain. Through green advertising efforts, the manufacturer and the retailer push up the consumers’ environmental consciousness and the return rate of the end-of-use products. Based on the manufacture directing Stackelberg game theory, this research looks into three different green advertising decisions (noncooperative, unilateral cooperative, and bilateral cooperative) under wholesale price contract, revenue-sharing contract, and financial support contract in the O2O CLSC. The results show that the bilateral cooperative incentive strategy always makes both the manufacturer and the retailer invest more in green advertising efforts and increase profits. Without affecting sales, implementing the bilateral cooperative incentive mechanism under the financial support contract is the best strategy to mitigate channel conflict, promote Pareto improvement, and ultimately achieve sustainable development goals.